Evaluasi Kerusakan Perkerasan Lentur Menggunakan Metode Bina Marga : Studi Kasus Jalan Towua Di Kota Palu Km 0 + 000 - Km 1 + 000 - Afrinaldy Andara; Muh. Ryan Pratama; Ainun Jariah Hilal Anshary; Andi Subhan Nur (Jurnal Konstruksi, 2026)
Initial survey results on Towua Road (Sta. Km 0+000–Km 1+000) indicate that the flexible pavement has experienced various forms of damage, including surface layer stripping, aggregate loss, split damage, and cracking. These conditions not only reduce driving comfort but also have the potential to compromise road user safety if not handled properly. This study aims to evaluate the types and levels of flexible pavement damage, determine the priority value for damage handling based on the Bina Marga method, and identify the factors causing the damage as a basis for formulating maintenance recommendations for Towua Road. The research method was conducted through a visual field survey on observation segments according to stationing (Sta.), after which the damage data were analyzed using the Bina Marga assessment procedure to obtain the percentage of pavement damage and the Priority Order (PO) for maintenance handling. Based on the analysis results, the total percentage of pavement damage was recorded at 45.84 percent, equivalent to 4,125.88 m² of the total observed road area. The obtained priority value was PO = 3, indicating that the road condition is classified as severely damaged and therefore requires pavement improvement treatment. Accordingly, the recommended action for Towua Road is overlay resurfacing (additional pavement layer) to restore road service performance and improve user comfort and safety.